Efisiensi Teknis Usaha Tani Kopi Arabika Garut Kuning (AGK) - Bedy Sudjarmoko; Enny Randriani (Jurnal Tanaman Industri dan Penyegar, 2019)
Coffee is one of the strategic commodities in West Java for its important economic role in West Java. However, studies on coffee farming efficiency are still rarely found.  Information on efficiency is critical because it affects the benefits the coffee farmers gain and its development program. This study aimed to investigate factors affecting the technical efficiency and technical efficiency level of Arabica Garut Kuning (AGK) coffee farming in Garut Regency, carried out from June to September 2016 using survey methods. Research location was determined by purposive sampling and 72 respondents were randomly chosen from Arabica coffee farmer population in Garut Regency. The data was analysed using stochastic frontier production, estimated by Maximum Likelihood Estimates (MLE) method. The results showed that the factors influencing the technical efficiency of coffee farming are land area, use of Urea fertilizer, ZA fertilizer, SP 36 fertilizer, herbicide and labor. The technical efficiency of farmers is quite high (average of 0.81). Means farmers have been technically efficient especially in allocating resources and utilizing existing cultivation technology. To further improve the technical efficiency as well as its revenue share of AGK, support from local governments and other stakeholders is still urgently needed.